(untitled) (Asian-Australasian Journal of Food Safety and Security, 2017)
The present study was carried out to evaluate the comparative capability of producing infections and causing mortality of the experimental Magur (Clarias batrachus) with motile Aeromonas species. A total of 200 apparently healthy C. batrachus were acclimatized to the laboratory conditions for experimental study. Nine different groups (each group consisting of 20 fish) of healthy C. batrachus was injected with nine motile Aeromonas isolates (A. hydrophila-3, A. sobria-3 and A. caviae-3). Experimental C. batrachus were infected with motile A. hydrophila, A. sobria and A. caviae to groups 1-3, 4-6 and 7-9, respectively while group 10 was injected with sterile physiological saline (0.85% NaCl) and served as the control. The selected motile bacterial species via intramuscularly were injected at the rate of 4.5 × 105 cfu/fish for pathogenicity study on C. batrachus and monitored up to two weeks. The highest clinical infections were noticed 90% in group-3 whereas only 35% in group-8 within the experimental period. After two weeks of the experiment, the cumulative mortality rate was also found highest (60%) in group-3 but lowest (15%) in group-9 while no infection or mortality showed in group-10 (control group). The development of infection and mortality to the injected C. batrachus was associated more severely by Aeromonas hydrophila than A. sobria and A. caviae used in this study. However, the isolates motile Aeromonas species could serve as the primary cause of skin lesions as well as mortality in cultured C. batrachus. Asian Australas. J. Food Saf. Secur. 2017, 1 (1), 45-50